2019
DOI: 10.1097/cej.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing identified somatic alterations that may underlie the etiology of Chinese papillary thyroid carcinoma

Abstract: To better understand the etiology of papillary thyroid carcinoma, we did next-generation sequencing for the exomes and transcriptomes of a Chinese cohort of 28 pairs of DNA and RNA samples extracted from papillary thyroid carcinoma tumors and adjacent normal thyroid samples. The Chinese papillary thyroid carcinoma tumors harbored somatic mutations in the known driver genes, such as KRAS, TP53, BRAF, ERBB2, and MET. In addition, we identified novel papillary thyroid carcinoma candidate genes that had not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We found that, beyond regulating the expression levels of numerous genes, prostate cancer altered also the cellular homeostatic mechanisms that control the abundances of their transcripts and, more importantly, their networking in functional pathways. Interestingly, even equally histopathologically graded cancer nodules from the same tumor have different transcriptomic organizations that go beyond the recognized tumor heterogeneity of gene expression levels (e.g., [ 32 , 33 , 34 ]). This conclusion raises serious concerns about the validity of biomarkers identified through meta-analyses of large populations of cancer-stricken and cancer-free humans and poses new challenges for the germline genetic testing of prostate cancer patients [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that, beyond regulating the expression levels of numerous genes, prostate cancer altered also the cellular homeostatic mechanisms that control the abundances of their transcripts and, more importantly, their networking in functional pathways. Interestingly, even equally histopathologically graded cancer nodules from the same tumor have different transcriptomic organizations that go beyond the recognized tumor heterogeneity of gene expression levels (e.g., [ 32 , 33 , 34 ]). This conclusion raises serious concerns about the validity of biomarkers identified through meta-analyses of large populations of cancer-stricken and cancer-free humans and poses new challenges for the germline genetic testing of prostate cancer patients [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although histologically similar, the unrepeatable combination of the “other” regulated/mutated genes makes the cancer of each individual unique. Therefore, whenever possible, one should refer the gene expression profile in cancer nodules to that of the surrounding cancer-free tissue of the same tumor (e.g., [ 31 , 32 , 33 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic profiling of PTC samples compared to adjacent normal thyroid tissues identified the Nrf2-mediated oxidative stress response as one of six commonly upregulated oncogenic pathways [66]. Somatic mutations in KEAP1, NFE2L2, or other Nrf2 pathway components were not reported in this study, which is not surprising, knowing that the frequency of such mutations in thyroid cancer is lower than in other cancer types with activated Nrf2 signaling [64,65], and given the small sample size of the specific study [66].…”
Section: Thyroid Carcinomasmentioning
confidence: 68%
“…Transcriptomic profiling of PTC samples compared to adjacent normal thyroid tissues identified the Nrf2-mediated oxidative stress response as one of six commonly upregulated oncogenic pathways [66]. Somatic mutations in KEAP1, NFE2L2, or other Nrf2 pathway components were not reported in this study, which is not surprising, knowing that the frequency of such mutations in thyroid cancer is lower than in other cancer types with activated Nrf2 signaling [64,65], and given the small sample size of the specific study [66]. Another study found higher Nrf2 mRNA levels and Nrf2 protein abundance in PTC samples compared to normal tissues [67]; of note, Nrf2 is known to induce the transcription of its own gene (at least in the mouse), via an ARE element in the gene promoter [68].…”
Section: Thyroid Carcinomasmentioning
confidence: 99%
“…In our study, we constructed a recurrence risk model with methylation profiles of SPTA1, APCS, and DAB2 by stepwise multivariable Cox regression with data from TCGA. SPTA1, which have been linked to hereditary elliptocytosis and hereditary spherocytosis [45], were reported as a possible tumor driver gene in prostate cancer [46] and papillary thyroid carcinoma [47]. APCS is a gene that codes serum amyloid P-component, which is one of the main acute-phase 17 Disease Markers reactants and has reported to a biomarker for survival in nonsmall cell lung cancer after thoracic radiotherapy [48].…”
Section: Discussionmentioning
confidence: 99%